2019
DOI: 10.1021/acs.macromol.8b02600
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition from Tetragonal Form II to Hexagonal Form I of Butene-1/4-Methyl-1-pentene Random Copolymers: Molecular Factor versus Stretching Stimuli

Abstract: The phase transition from the kinetically favored tetragonal form II into the thermodynamically stable hexagonal form I is the general phenomenon and core issue in application of polybutene-1-based materials. It is known that the variation of molecular structure by copolymerizing counits and the imposition of external stretching both greatly affect the phase transition. In this work, a series of butene-1/4-methyl-1-pentene (4M1P) random copolymers were synthesized with the dimethylpyridyl­amidohafnium/organobo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 70 publications
(122 reference statements)
0
66
0
Order By: Relevance
“…However, Form I′, described as a defective Form I with lower melting temperature, can be formed through special crystallization procedures, such as solution crystallization, blending with iPP, or copolymerization with other monomers . Actually, quiescent aging at room temperature of Form II samples is generally used for generating trigonal Form I, where the molecular conformation of the chains is that of a 3/1 helix …”
Section: Introductionmentioning
confidence: 99%
“…However, Form I′, described as a defective Form I with lower melting temperature, can be formed through special crystallization procedures, such as solution crystallization, blending with iPP, or copolymerization with other monomers . Actually, quiescent aging at room temperature of Form II samples is generally used for generating trigonal Form I, where the molecular conformation of the chains is that of a 3/1 helix …”
Section: Introductionmentioning
confidence: 99%
“…However, recent investigation seems to support the latter one. It was found that the stress dominating the phase transition is the stress perpendicular to the helical stem …”
Section: Discussionmentioning
confidence: 99%
“…Even, they found that without annealing at a lower temperature, form II could also transform to form I rapidly in a low molecular weight of PB‐1 synthesized by themselves, which chain was too short to form intercrystalline links . Moreover, Ma et al found that the stress dominating the phase transition was not the stress parallel to the normal direction of the lamellar stack but the stress perpendicular to the normal direction . Seemingly, these findings are completely contrary to the classical view.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations